Exploring the role of teams and technology in patients' medication decision making - Mercer, Kathryn; Guirguis, Lisa; Burns, Catherine; Chin, Jessie; Dogba, Maman Joyce; Dolovich, Lisa; Guénette, Line; Jenkins, Laurie; Légaré, France; McKinnon, Annette; McMurray, Josephine; Waked, Khrystine; et al. (Elsevier, 2019)
We know little about how electronic health records (EHRs) should be designed to help patients, pharmacists, and physicians participate in interprofessional shared decision making. We used a qualitative approach to understand better how patients make decisions with their health care team, how this information influences decision making about their medications, and finally, how this process can be improved through the use of EHRs.
The final publication is available at Elsevier via https://doi.org/10.1016/j.japh.2018.12.010. © 2019. This manuscript version is made available under the CC-BY-NC-ND 4.0 license http://creativecommons.org/licenses/by-nc-nd/4.0/
Keywords: electronic health records; decisionmaking; pharmacy